Politicians and climate change: a systematic review of the literature - Moore, Brendan; Geese, Lucas; Kenny, John; Dudley, Harriet; Jordan, Andrew; Prados Pascual, Alba; Lorenzoni, Irene; Bulian, Simon; Enguer, Joan; Tosun, Jale (Wiley interdisciplinary reviews. Climate change, 2024)
Politicians' engagement with climate change is the focus of an emerging literature, but this research has not been subjected to systematic analysis. To address this important gap, we perform a systematic review of 141 articles on politicians and climate change published between 1985 and 2021. We find a growing research area; almost half of the articles were published after 2018. Existing research is fragmented and focused on a small number of democracies in the Global North, with the United States, United Kingdom, Germany, Norway and Australia being the most-heavily studied. Substantively, we analyze politicians' motivations, the incentives and barriers they face, and the strategies they employ to block/enable climate action. We find evidence of politicians being both intrinsically and extrinsically motivated. Intrinsic motivations often derive from formative experiences occurring prior to entering politics. Extrinsic motivations most commonly include publics/voters and external events. Importantly, intrinsic and extrinsic motivations vary in different political contexts, and indeed these two motivations may pull politicians in different directions. Politicians may employ various strategies—such as reframing—to achieve their desired policy outcomes. Moreover, politicians' motivations and strategies in relation to climate change are not static, but often vary. We conclude that there is an urgent need for research on how politicians are enabled and/or constrained by political system characteristics. Research is especially called for in the Global South and/or less democratic systems, as well as on investigating how politicians are (not) decarbonizing difficult-to-abate sectors and how they reconcile the sometimes-competing demands for climate change mitigation and adaptation. This article is categorized under: Policy and Governance > National Climate Change Policy Policy and Governance > Multilevel and Transnational Climate Change Governance
Zuerst veröffentlicht: 07. Juli 2024
Gesehen am 20.12.2024